Peran Kyai Pondok Pesantren Faidlul Qur’an Jombang Sebagai Pengganti Orang Tua - Muhammad Nur Cholis Al Mutawakil; Moh. Makmun; Agus Mahfudin (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study was motivated by the important role of the kyai in the life of a pesantren, who serves not only as the leader of an Islamic educational institution but also as a surrogate parent for the students. This study aims to analyze the role of the kyai at the Faidlul Qur’an Islamic Boarding School and to explain his function as a surrogate parent for the students. The research method used was qualitative, employing a case study approach. Data were collected through observation, interviews, and documentation, and were subsequently analyzed using the Miles and Huberman model. The results indicate that the kyai fulfills four primary roles: as the pesantren’s leader, a Quran instructor, a community religious figure, and a caregiver for the students. In their role as surrogate parents, the kyai meet the students’ educational, emotional, and spiritual needs through guidance, supervision, setting a good example, providing attention, and fostering moral character. These findings indicate that the kyai’s role makes a significant contribution to the formation and development of the students’ education, emotional well-being, and spirituality.